Reaching revelatory places: the role of solicited diaries in extending research on emotional geographies into the unfamiliar. Issue 4 (20th August 2015) - Filep, Crystal V; Thompson‐Fawcett, Michelle; Fitzsimons, Sean; Turner, Sarah
Abstract : Solicited diaries can be used to delve into otherwise unreachable interpretations of social and physical experiences. Diaries help researchers to understand the embodied and the emotional in human geography. In this paper we develop on the work of multiple disciplines, enhancing the rationale as to why and how to employ diaries, and highlighting the benefits and drawbacks associated with this methodological tool. Notably, we extend the literature related to solicited diaries into the unfamiliar through examples from our research with scientists working in Antarctica who maintained diaries for us. We illustrate the potential for such diaries to elicit meaningful narratives that complement and extend data collected through interviews. Diaries provide timely, in situ space for emotional reactions to and contemplations of the immediate environment, as well as on every day and out of the ordinary events, while interviews provide interviewees with time and distance from the field to offer reflections based on lasting impressions. In particular, when combined, solicited diaries and interviews can substantially enrich investigations of those innately human, yet often elusive, places of the mind – revelatory places – in‐between people and the environments that move them.